Industrial training report: Lembaga Tabung Haji, Sitiawan / Najihah Iman Shaiful Faisal - Shaiful Faisal, Najihah Iman (Universiti Teknologi MARA, Perlis, 2024)
My impactful and educational 24-week internship at Lembaga Tabung Haji in Sitiawan, Perak, from March 4 to August 12, 2024, offered a valuable opportunity for both personal and professional development. Assigned to the Depositors Services and Operations Department under the leadership of Tuan Haji Mohd Faizal bin Jamil, I focused on enhancing customer satisfaction and developing conflict resolution skills, recognizing the direct link between excellent customer service and positive outcomes. Throughout my internship, I actively contributed to the department's goals by handling customer service and data management tasks. My responsibilities included assisting with account creation and management, resolving TH account issues, explaining the benefits of virtual account opening, and providing guidance on kiosk navigation. This hands-on experience allowed me to directly contribute to departmental objectives and equipped me with valuable new skills. I learned the importance of clear communication, patience, and attention to detail while assisting clients. Additionally, collaborating closely with team members, I provided feedback to improve service quality and ensured smooth operations. Through engaging projects, I gained extensive insight into TH's products and services, which reinforced my academic knowledge and sparked a deep interest in the Human Resources field, further solidifying my commitment to a career in this area.